Analysis of Vitamin D Receptor Polymorphisms in Patients with Familial Multiple Sclerosis - Yucel, Fatma Ebru (Med Arch, 2018)
OBJECTIVE: Genetic and environmental factors are important in the development of the multiple sclerosis (MS). Vitamin D shows its effects on the immune system with the vitamin D receptor (VDR) in the nucleus. Single nucleotide polymorphisms (SNPs) in the VDR gene can lead to alterations in vitamin D functions and metabolism.Taq I, Apa I, Fok I and Bsm I polymorphisms and MS associations have been investigated in many studies. VDR gene polymorphism has not been previously studied in patients with familial MS. AIM: We aimed to investigate the relationship between familial MS patients present in Turkish population and VDR genotypes Taq I, Apa I and Fok I polymorphisms. METHODS: 29 patients with a family history of MS and 120 healthy control subjects were included in the present study. We studied present VDR genotypes Taq I, Apa I and Fok I polymorphisms. RESULTS: We observed a significant difference between controls and patient group only in Taq I polymorphism (p: 0.025). Homozygousity of G allele was not seen in the patients whereas in controls frequency of that genotype was p:0.208. When gender was considered males show significant difference for GG genotype. There were no significant association for the Apa I and Fok I polymorphisms. CONCLUSION: Although our findings suggest association between VDR Taq I polymorphism and the familial MS, additional studies are needed to establish detailed relationships.